GE_GERICHTE P/1193/2020 vom 26. Februar 2020 - GE Cour de justice (2020)
DIFFAMATION;CALOMNIE;ABUS DE POUVOIR;ENLÈVEMENT(INFRACTION);CONTRAINTE(DROIT PÉNAL);PROTECTION DES DONNÉES | cp.173; cp.174; cp.312; cp.181; cp.183; lpd.35; lpd.2